2023
DOI: 10.1055/a-2028-8214
|View full text |Cite
|
Sign up to set email alerts
|

The Benefit of Transvaginal Elastography in Detecting Deep Endometriosis: A Feasibility Study

Abstract: Objectives: This study aimed to evaluate elastography features of deep infiltrating endometriosis (DIE), and to define whether this technique may discriminate lesions from surrounding non-endometriotic tissue. Methods: This was an exploratory observational study on women affected by DIE treated in a third-level academic hospital gynaecology outpatient facility between 2020 and 2021. Strain elastography (SE) was conducted via transvaginal probe. Tissue deformation of DIE and surrounding tissue was expressed as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Although the classification system was relatively comprehensive and showed good interobserver agreement, it did not incorporate the elastography findings and may not be convenient for clinical application. Our results and those of some previous studies have demonstrated the value of elastography in diagnosing and assessing the severity of endometriosis and adenomyosis [ 6 , 11 , 21 23 ]. Elastography is also valuable in evaluating the efficacy of conservative treatment.…”
Section: Discussionsupporting
confidence: 83%
“…Although the classification system was relatively comprehensive and showed good interobserver agreement, it did not incorporate the elastography findings and may not be convenient for clinical application. Our results and those of some previous studies have demonstrated the value of elastography in diagnosing and assessing the severity of endometriosis and adenomyosis [ 6 , 11 , 21 23 ]. Elastography is also valuable in evaluating the efficacy of conservative treatment.…”
Section: Discussionsupporting
confidence: 83%
“…Multiple logistic regression analysis showed that the presence of DIE did not affect symptoms manifestation following COVID-19 vaccination. In contrast to adenomyosis or ovarian endometriosis, DIE is mostly composed by a stiff highly fibrotic scar tissue [35], with little residual immune and inflammatory activity. Accordingly immune activation following COVID-19 vaccination, is presumably too little represented in DIE to play a significant role on symptom manifestation.…”
Section: Discussionmentioning
confidence: 99%
“…Strain elastography is an additional diagnostic modality employed for the evaluation of endometriosis. Xholli et al discuss the utilization of elastography, a technology with the ability to quantitatively assess tissue structure and elasticity, in the identification or the monitoring of the progression of established DIE nodules [28]. Brunelli et al emphasize the significant role of elastography in the accurate diagnosis of deep pelvic endometriosis lesions, exhibiting high sensitivity and specificity [29].…”
Section: Discussionmentioning
confidence: 99%